Validation of the German version of the Mediterranean Diet Adherence Screener (MEDAS) questionnaire - Hebestreit, Katrin; Yahiaoui-Doktor, Maryam; Engel, Christoph; Vetter, Walter; Siniatchkin, Michael; Erickson, Nicole; Halle, Martin; Kiechle, Marion; Bischoff, Stephan C. (BMC Cancer, 2017)
Background: Health benefits of the Mediterranean Diet (MD) have been shown in different at-risk populations. A German translation of the Mediterranean Diet Adherence Screener (MEDAS) from the PREvención con DIeta MEDiterránea (PREDIMED) consortium was used in the LIBRE study, investigating effects of lifestyle-intervention on women with BRCA1/2 mutations. The purpose of the present study is to validate the MEDAS German version. Methods: LIBRE is a multicentre (three university hospitals during this pilot phase), unblinded, randomized, controlled clinical trial. Women with a BRCA1/2 mutation of age 18 or over who provided written consent were eligible for the trial. As part of the assessment, all were given a full-length Food Frequency Questionnaire (FFQ) and MEDAS at baseline and after 3 months. Data derived from FFQ was compared to MEDAS in order to evaluate agreement or concordance between the two questionnaires. Additionally, the association of dietary intake biomarkers in the blood (β-carotene, omega-3, omega-6 and omega-9 fatty acids and high-sensitivity C-reactive protein (hsCRP)) with some MEDAS items was analyzed using t-Tests and a multivariate regression. Results: The participants of the LIBRE pilot study were 68 in total (33 Intervention, 35 Control). Only participants who completed both questionnaires were included in this analysis (baseline: 66, month three: 54). The concordance between these two questionnaires varied between the items (Intraclass correlation coefficient of 0.91 for pulses at the highest and -0.33 for sugar-sweetened drinks). Mean MEDAS scores (sum of all items) were 9% higher than their FFQ counter-parts at baseline and 15% after 3 months. Higher fish consumption (at least 3 portions) was associated with lower omega-6 fatty acid levels (p = 0.026) and higher omega-3 fatty acid levels (p = 0.037), both results being statistically significant. Conclusions: We conclude that the German MEDAS in its current version could be a useful tool in clinical trials and in practice to assess adherence to MD. Trial registration:ClinicalTrials.gov , registered on March 12, 2014, identifier: NCT02087592. World Health Organization Trial Registration, registered on 3 August 2015, identifier: NCT02087592.
CRIS-Team Scopus Importer:2023-03-08
Keywords: BRCA1/2; Food frequency; Hereditary breast cancer; Mediterranean diet adherence; Validation